PENDIDIKAN AKHLAK PADA KEGIATAN PENDIDIKAN KARAKTER MATERI SEJARAH KEBUDAYAAN ISLAM DI SMPN 10 BANJARBARU - Nurul Qomariyah; Muhammad Baidhawi (AL-FALAH: Jurnal Keislaman dan Kemasyarakatan, 2025)
This study discusses "Ethical Education in Character Education Activities on Islamic Cultural History at SMPN 10 Banjarbaru." The purpose of this study was to determine how Moral Education is implemented in Character Education Activities on Islamic Cultural History at SMPN 10 Banjarbaru and to identify the supporting and inhibiting factors. The subjects in this study were two Islamic Religious Education teachers involved in Moral Education in Character Education Activities on Islamic Cultural History. The object of this research is Character Education Activities in Islamic Cultural History. The purpose of this study was to determine the effectiveness of Moral Education in Character Education activities in Islamic Cultural History at SMPN 10 Banjarbaru, along with the supporting and inhibiting factors. The author used observation, interviews, and documentation techniques to collect data. Data processing techniques included editing, classification, and interpretation, using descriptive and qualitative methods, followed by analysis. Conclusions were drawn using deductive methods. Based on the research results, it is known that Moral Education in Character Education Activities in Islamic Cultural History at SMPN 10 Banjarbaru has been implemented effectively. The moral education gained through Islamic Cultural History has also been applied by students, including the values ​​of Shidiq, Tabligh, Amanah, and Fathonah. This implementation is not only within the school environment but also in daily life. Supporting and inhibiting factors include the Islamic Religious Education (PAI) teacher as the facilitator of the Islamic Cultural History material and the teaching staff as the facilitator, the Character Education Activities, and the students.